Linking High-z and Low-z: Are We Observing the Progenitors of the Milky Way with JWST? - Elka Rusta; Stefania Salvadori; Viola Gelli; Ioanna Koutsouridou; Alessandro Marconi (The Astrophysical Journal Letters)
The recent JWST observation of the Firefly Sparkle at z = 8.3 offers a unique opportunity to link the high- and the low- z Universe. Indeed, the claim of it being a Milky Way (MW) type of assembly at the cosmic dawn opens the possibility of interpreting the observation with locally calibrated galaxy-formation models. Here, we use the a state-of-the-art MW-evolution model to perform forward modeling of our Galaxy's progenitors at high- z . We build a set of mock spectra for the MW building blocks to make predictions for JWST and to interpret the Firefly Sparkle observation. First, we find that the most massive MW progenitor becomes detectable in a deep survey like JADES from z ≈ 8.2, meaning that we could have already observed MW analogs that still need interpretation. Second, we provide predictions for the number of detectable MW progenitors in lensed surveys like the CAnadian NIRISS Unbiased Cluster Survey, and interpret the Firefly Sparkle as a group of MW building blocks. Both the number of detections and the observed NIRCam photometry are consistent with our predictions. By identifying the MW progenitors whose mock photometry best fits the data, we find bursty and extended star formation histories, lasting >150–300 Myr, and estimate their properties: M _h ≈ 10 ^8−9 M _⊙ , M _⋆ ≈ 10 ^6.2−7.5 M _⊙ , SFR ≈ 0.04–0.20 M _⊙ yr ^−1 , and Z _gas ≈ 0.04–0.24 Z _⊙ . Uncovering the properties of MW analogs at cosmic dawn by combining JWST observations and locally constrained models will allow us to understand our Galaxy's formation, linking the high- and low- z perspectives.